DAMPAK PERBAIKAN TANGGUL SEBAGAI ADAPTASI BANJIR ROB TERHADAP PENGEMBANGAN UMKM DAN KEBERLANJUTAN EKONOMI MASYARAKAT PESISIR DI KEPULAUAN SELAYAR - Annisar Eka Putri; Dalilul Falihin; Rusdi (STKIP Subang, 2026)
The coastal areas of the Selayar Islands are vulnerable to tidal flooding, which impacts the environment and the economic activities of coastal communities. Repairing embankments is one form of adaptation being undertaken to reduce this risk. This study aims to examine the description of embankment repairs as an adaptation effort by coastal communities, analyze their impact on the development of Micro, Small, and Medium Enterprises, and assess their contribution to maintaining the economic sustainability of coastal communities in the Selayar Islands. This study uses a qualitative approach with a case study type. Data collection was conducted through observation, interviews, surveys, and documentation. The results show that embankment repairs contribute to improving coastal environmental resilience through flood and coastal erosion control, supported by embankment structure reinforcement, wave breaker construction, and additional drainage channels. In addition, embankment improvements have a positive impact on increasing community economic activity, particularly strengthening the micro, small, and medium enterprise sector. The existence of embankments also plays a role in improving environmental safety and the smooth running of economic activities, thereby supporting the sustainable economy of coastal communities.